Nanoparticle-targeted photoacoustic cavitation for tissue imaging - McLaughlan, J; Roy, R; Ju, H; Murray, T (Society of Photo-optical Instrumentation Engineers, 2010)
Photoacoustic tomography is a non-invasive imaging technique based on the detection of broadband acoustic emissions generated by the absorption of light in tissue. This technique utilises the high contrast of optical imaging with high resolution from ultrasound imaging. However, the ability to detect these emissions above the noise level ultimately limits the depth to which imaging can be performed. Introduction of light-absorbing gold nanoparticles can improve the signal-to-noise ratio in tissue, through greater optical absorption and targeting specific cell populations, thereby enhancing contrast and the ability to delineate tissue types. For sufficiently high laser fluence incident on a nanoparticle, a transient vapour cavity is formed and undergoes inertial collapse, generating a broadband emission and possibly additional contrast. However, the laser fluence required to achieve this typically exceeds the maximum permissible exposure (MPE) for tissue. Through the combination of ultrasonic and optical pulses, the light and sound thresholds required to repeatedly generate inertial cavitation were reduced to 11.1 mJ/cm2 and 1.5 MPa respectively. Experiments employed a transparent acrylamide gel possessing a small (<600 μm) spherical region doped with 80 nm diameter gold nanoparticles and simultaneously exposed to pulsed laser light (532 nm) and pulsed ultrasound (1.1 MHz). The amplitude of broadband emissions induced by both light and sound exceeded that produced by light alone by almost two orders of magnitude, thereby facilitating imaging a deeper depth within tissue. 2D images of doped regions generated from conventional photoacoustic and ultrasound-enhanced emissions are presented and compared.